Redefinition of two little known mirine plant bug genera Babacoris and Paramiridius (Hemiptera: Heteroptera: Miridae: Mirinae) - Yasunaga, Tomohide; Tsai, Jing-Fu; Yamada, Kazutaka (Zootaxa, 2018)
A long neglected plant bug genus Babacoris Miyamoto, 1994 (Mirinae: Mirini), proposed for a single Taiwanese species, B. striatus Miyamoto, is redefined and redescribed as a valid genus, based on recent rediscovery of the type species from Hengchun, Taiwan; the neotype is designated for B. striatus. The genus is now presumed to be closely related to Paramiridius Miyamoto & Yasunaga which also has been poorly known since the original description. A species recently described from Laos, Babacoris laomontanus (Oh, Yasunaga & Lee) comb. n., is transferred from Paramiridius. An updated checklist of the tribe Mirini in Taiwan is incorporated, with proposition of a new combination, Adelphocorisella minutum (Poppius) comb. n., having been left in Megacoelum Fieber as incertae sedis.